Lipid Profile Parameters and Adipokines among Adolescents Infected with Toxoplasmosis - Al-Halbousi, Yousif Riyadh Shakir; Al-Warid, Harith Saeed (Iraqi Journal of Science, 2024)
The lipid profile and adipokines of an adolescent may be affected by some parasite infections. Recently, it has been discovered that these parasites are connected to body mass index (BMI), lipids and adipokines. The current study, therefore, aimed to specify how Toxoplasma gondii (T. gondii) affect BMI, lipid profile and adipokines. This study was conducted in Al Madain hospital, Baghdad from October to December 2022. An ELISA test was performed to examine the anti-T. gondii IgG and IgM for a group of adolescents attending the hospital. Based on this examination ninety adolescents were chosen to be involved in the study. They were separated in to two groups: individuals who tested positive for the parasite (n=45) and those who tested negative for the parasite, control group (n=45). All participating adolescents were subjected to some measurements which included body mass index (BMI), lipid profile parameters (cholesterol, triglycerides, HDL, LDL, and VLD) and adipokines (adiponectin and chemerin). Significant high BMI was noticed in T. gondii positive group (29.65±0.6 Kg/m2) compared to control. The results also indicated that there was a significant increase in all tests of the lipid profile among T. gondii positive group compared to the control. However, the matter reversed in HDL examination as its level increased significantly in the control compared to the T. gondii positive group. Finally, both adiponectin (78.6±0.037 ng/ml) and chemerin (3.43±0.1 ng/ml) raised up significantly in T. gondii positive group versus control group.